Genome-wide analysis of Nicotiana tabacum IDD genes identifies NtIDD9 as a regulator of leaf angle - Li, Zefeng; Cao, Peijian; Liu, Huabing; Zhang, Jianfeng; Luo, Zhaopeng; Zhang, Hui; Wu, Mingzhu; Xie, Xiaodong (Frontiers in Plant Science, 2024)
The INDETERMINATE DOMAIN (IDD) gene family, encoding a class of C2H2 transcription factor, played diverse roles in land plants. The IDD family in tobacco (Nicotiana tabacum) has not been characterized. In this study, 26 NtIDDs were identified in the tobacco genome. Phylogenetic analysis showed that NtIDDs were divided into five groups. Motif analysis revealed that the ID domain was conserved in NtIDDs. Gene duplication analysis demonstrated that segmental/whole-genome duplication and dispersed duplication would have occurred in NtIDDs. Cis-element analysis predicted that hormone-, stress-, and development-related elements are located in NtIDD promoters. Expression analysis revealed tissue preference patterns and differential hormone responses in NtIDDs. Further investigations on the function of NtIDD9 exhibited increased leaf angle degrees in RNA silencing plants. Cellular localization suggested that NtIDD9 expressed in the endodermis of the leaf petiole base. Subcellular localization analysis revealed that the NtIDD9 protein was located in the nucleus. Hormone quantification found that the levels of auxin, ABA, JA, and GA were significantly changed in NtIDD9-silenced plants. Thus, the study suggested that NtIDD9 played a crucial role in modulation of leaf angle development. Overall, these findings lay foundations for future function and mechanism research on IDDs in tobacco.